Digital inclusion as a tool to overcome economic inequality in the context of digital transformation digital inclusion as a tool to overcome economic inequality in the context of digital transformation - Voitsekhovska, A.; Lomachynska, I. (Journal of Education, Health and Sport, 2025)
In the article explores digital inclusion as a key tool for overcoming economic inequalities in the context of digital transformation. Examples of international initiatives that demonstrate the practical implementation of digital inclusion policies, in particular programs in Singapore, Great Britain, USA. The importance of intersectoral cooperation between the state, business, civil society and themselves citizens in creating an inclusive digital space. The article emphasizes the importance of the need for a holistic digital policy as a prerequisite for a fair socio-economic development. Particular attention is paid to practical applications for the effective implementation of digital initiatives in a global context.